2011
DOI: 10.1088/0953-8984/23/7/075402
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneities in CuZr-based bulk metallic glasses studied by x-ray scattering

Abstract: Inhomogeneities in two CuZr-based bulk metallic glasses (BMGs) were studied by using synchrotron radiation x-ray scattering techniques. (Cu(4.5/5.5)Ag(1/5.5))(46)Zr(46)Al(8) BMG was found to be more inhomogeneous than Cu(46)Zr(46)Al(8) BMG on the small length scale, where Cu and Ag atoms form enriched zones. Such heterogeneities are locally favorable for forming close-packed icosahedron-like clusters in three-dimensional space, greatly promoting the glass forming ability of this alloy. Upon annealing near the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…For instance, in Zr 48 Cu 36 Ag 8 Al 8 , the atomic ratio between Zr and Cu is 48:36 (4:3), while 7.56 Zr atoms and 4.97 Cu atoms (3:2, which is apparently larger than 4:3) surround about Ag centers; in Zr 48 Cu 29 Ag 15 Al 8 , the atomic ratio between Zr and Cu is 48:29 (about 8:5), while 7.28 Zr atoms and 3.19 Cu atoms (2.2:1, which is obviously larger than 8:5) are neighbored around Ag centers. This is quite consistent with the experimental observation of separation between Cu-enriched and Ag-enriched amorphous phases in ZrCuAl(Ag) multicomponent MGs [35,36]. This also indicates that the RMC simulation method can provide reliable structural model of MGs.…”
Section: Information Obtained From Rmc Simulated Structural Modelsupporting
confidence: 89%
“…For instance, in Zr 48 Cu 36 Ag 8 Al 8 , the atomic ratio between Zr and Cu is 48:36 (4:3), while 7.56 Zr atoms and 4.97 Cu atoms (3:2, which is apparently larger than 4:3) surround about Ag centers; in Zr 48 Cu 29 Ag 15 Al 8 , the atomic ratio between Zr and Cu is 48:29 (about 8:5), while 7.28 Zr atoms and 3.19 Cu atoms (2.2:1, which is obviously larger than 8:5) are neighbored around Ag centers. This is quite consistent with the experimental observation of separation between Cu-enriched and Ag-enriched amorphous phases in ZrCuAl(Ag) multicomponent MGs [35,36]. This also indicates that the RMC simulation method can provide reliable structural model of MGs.…”
Section: Information Obtained From Rmc Simulated Structural Modelsupporting
confidence: 89%
“…We thus performed SAXS measurements for 5 monolithic MG samples in Figure , in which the scattering intensity I ( q ) vs q follows a power–law relationship, I ( q ) ∼ (1/ q ) D . ,, However, for different MGs, q ranges in which the power–law relationship exists are different. By taking a similar q range of about 0.008–0.025 Å –1 ( 2 π /q ≈ 250–785 Å), all five studied MG samples follow the power–law with scaling exponents of D = 2.71 ± 0.15, 2.72 ± 0.25, 2.49 ± 0.25, 2.64 ± 0.15, and 2.57 ± 0.25 for Cu 45 Zr 46 Al 7.5 Ti 1.5 , Au 55 Cu 25 Si 20 , Au 55 Cu 25 Ag 5 Si 15 , Cu 46 Zr 46 Al 8 , and Zr 46 Cu 30.14 Ag 8.36 Al 8 Be 7.5 MGs, respectively, consistent with previous reports. It should be mentioned that scaling exponents deduced by fitting the range of linear part are almost similar within the experimental uncertainty. Although different MG samples have different q ranges exhibiting the power–law relationship, the normalized scattering intensity I ( q ), i.e., I ( q )/ I max , where I max is the maximum intensity of I ( q ) for each MG sample studied, as a function of the normalized q , i.e., q / q min , where q min is the minimum of q for each MG sample studied at which the power–law relationship starts, are plotted in Figure .…”
Section: Resultsmentioning
confidence: 96%
“…For examples, silica aerogels have a fractal dimension of about D = 2.4, D = 2.5 for porosity, D = 2.6 for cement, and D successively changing from 2.3 to 1.76 for protein–detergent complexes . Even for disordered metallic systems, the power–law relationship was also reported based on SAXS measurements, for example, D = 2.6 for a La–Zr–Al–Cu–Ni MG sample on a length scale of about 60–200 Å and D = 2.8 for CuZr-based MG samples on a scale of about 90–1200 Å. However, the understanding of fractal feature or noncubic power–law relationship in MGs is still controversial, although it is a basic issue linked with the atomic packing in MGs.…”
Section: Introductionmentioning
confidence: 78%
“…For the Cu-Zr system, simulations have demonstrated that local icosahedral clustering correlates with glass formation from the liquid state for certain compositions [10,15,17].…”
Section: Medium-range Structural Motifs In the Cu-zr Systemmentioning
confidence: 99%
“…An emerging consensus is that metallic glass displays short to medium range order arising from the packing of local clusters [10][11][12][13][14][15][16][17][18][19]. This suggests that the stability of certain local motifs can be used to characterize the energetic stability of the glassy system.…”
Section: Introductionmentioning
confidence: 99%